KEMAHIRAN MENULIS KARANGAN NARASI DALAM BAHASA INGGRIS MAHASISWA SEMESTER IV FAKULTAS ILMU BUDAYA JURUSAN SASTRA INGGRIS UNIVERSITAS SAM RATULANGI - TOOY, NOVIRA AMANDA JUSTITIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This skripsi, entitled â€œKemahiran Menulis Karangan Narasi Dalam Bahasa Inggris Mahasiswa Semester IV Jurusan Sastra Inggris Fakultas Ilmu Budaya Universitas Sam Ratulangiâ€ is an attempt to analyze the ability of the fourth semester English Department students in writing narrative essay. The data were taken from the studentsâ€™ writing assignment. All data were classified based on the Keraf (2003:45) were scored using analytic scoring from1 to 5 on five aspects of evaluation : spelling and punctuation, vocabulary/diction, sentence structure, composition organization and narrative essay characteristics, and the relationship between theme and contents of the essay. The research findings show that, (1) 86,67% of the students got the highest score in spelling and punctuation; (2) 93,33% in vocabulary/diction; (3) 63,33% in sentence structure; (4) in evaluation of composition organization and narrative essay characteristics, 16,67% of the students wrote the complete essay while 76,67% students did not write one part of the essay, e.g. introductory or closing paragraph; and (5) in the relationship between theme and the contents of the essay, 50% of the students got the highest score. In addition, the total average of all aspects of evaluation is 87,2%. However, it is suggested that teachers should help students in writing better narrative essays by guiding them to have complete parts of the essay. Â Â Keywords : Writing skill, narrative essay, essays.